Communication impairments in children in residential care: an overlooked aspect of their education and well-being? - Susan McCool (Scottish Journal of Residential Child Care)
It is the aim of this paper to explore an often-overlooked aspect of the education and well-being of children in residential care: the claim that there is a high rate of undetected communication impairment among children in 'public care'(Cross, 2004). Unmet communication need has serious effects on a child’s education (Audet and Tankersley, 1999). The impact extends beyond academic attainment to encompass important educational and developmental aspects such as emotions and relationships, behaviour and self-regulation and, more broadly, participation and inclusion. This paper outlines the nature of communication impairment, and examines the evidence for unidentified need among children in residential care. It then explores what happens when needs remain unmet. The paper concludes with consideration of why services may fail both to recognise and respond to these needs, and offers examples of how some services have tried to respond to these issues.